2018
DOI: 10.1016/j.schres.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Motion energy analysis reveals altered body movement in youth at risk for psychosis

Abstract: This study represents an innovative perspective on gross motor function in the UHR group. Importantly, the automated approach used in this study provides a sensitive and objective measure of body movement abnormalities, potentially guiding novel assessment and prevention of symptom development in those at risk for psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 72 publications
2
22
2
Order By: Relevance
“…Schizophrenia is conceived as a form of the same cerebellar cognitive affective syndrome, ie, as involving cerebellar dysfunctions. Our data are corresponding well to those concepts and suggest that the equilibriometric dysmetric and ataxic LMPs in schizophrenia are in fact subclinical equivalents of the cerebellar neurological signs and more specifically of the balance and motor coordination deficits, which are often revealed in schizophrenic patients and preschizophrenic high‐risk populations . Although indirectly, these subtle locomotor irregularities provide further evidence that schizophrenia is a brain disease, affecting functional neural circuits, which engage the prefrontal cortex, thalamus, basal ganglia, and cerebellum, as well as particular neurotransmitters, such as dopamine and glutamate .…”
Section: Translational Integrative Evaluation Of Individual Brain Dyssupporting
confidence: 87%
See 3 more Smart Citations
“…Schizophrenia is conceived as a form of the same cerebellar cognitive affective syndrome, ie, as involving cerebellar dysfunctions. Our data are corresponding well to those concepts and suggest that the equilibriometric dysmetric and ataxic LMPs in schizophrenia are in fact subclinical equivalents of the cerebellar neurological signs and more specifically of the balance and motor coordination deficits, which are often revealed in schizophrenic patients and preschizophrenic high‐risk populations . Although indirectly, these subtle locomotor irregularities provide further evidence that schizophrenia is a brain disease, affecting functional neural circuits, which engage the prefrontal cortex, thalamus, basal ganglia, and cerebellum, as well as particular neurotransmitters, such as dopamine and glutamate .…”
Section: Translational Integrative Evaluation Of Individual Brain Dyssupporting
confidence: 87%
“…With relatively few exceptions (limited to the most disorganized and severely psychotic or negativistic cases), the majority of patients follow the instructions and cooperate adequately during the test. Nowadays, it is already confirmed that the objectively evaluated neuromotor and psychomotor disturbances reflect the brain dysfunctions in schizophrenia more reliably than the subjective symptoms . Our research data provide further evidence that the treatment decisions for the individual schizophrenic patients are more correct if they are guided by the objectively measured LMPs .…”
Section: Clinical Implications Of the Translational Equilibriometric supporting
confidence: 67%
See 2 more Smart Citations
“…; in ecological psychology (Davis, Kay, Kondepudi, & Dixon, 2016); for the diagnosis of psychological disorders (Dean, Samson, Newberry, & Mittal, 2018;Dutschke et al, 2018;Kupper, Ramseyer, Hoffmann, Kalbermatten, & Tschacher, 2010;Kupper, Ramseyer, Hoffmann, & Tschacher, 2015); and in psychotherapy (Galbusera, Finn, & Fuchs, 2018;Paulick et al, 2018;Ramseyer, 2011Ramseyer, , 2013Ramseyer & Tschacher, 2011, 2016.…”
mentioning
confidence: 99%